Formation of Political and Civilization Identity of Dagestan in a Terms of the Conflict of Identities - Shamil Abdulaevich Alybegilov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article discusses the formation of political and civilizational identity, Dagestan in the context of civilization identity of Russia. Against the background of the struggle of two civilization projects Russia-European and Eurasian in Dagestan comes opposition and with the Islamic civilizational project. Conflict civilizational projects lies in the heart of the crisis of political identity, Dagestan.